The Role of Psychotherapies in the Management of General Health Symptoms among Parents and Teacher of Autism Spectrum Disorders Adolescents - Saima Khan, Sadaf Tabassum, Maria Rafique (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The current article’s goal is to emphasize the importance of psycho-therapeutic interventions in the management of general health symptoms (i.e., bodily symptoms, sleep and anxiety-related symptoms, inability to socialize, depression symptoms) among parents and teachers of autistic spectrum disorder adolescents. Method: The current study is based on an experimental design to lessen the general health symptoms of parents and teachers of adolescents with autism spectrum disorders. choosing appropriate friends, appropriate use of humor, entering a conversation, exiting a conversation, get-togethers, good sportsmanship, teasing and embarrassing feedback, bullying and bad reputations, handling disagreements, rumors, and gossip relaxation exercises were all used by clinical psychologists at various schools. The general health questionnaire (GHQ-28) scale was filled by both control and experimental group participants prior to the start of therapy. G power was used to calculate sample size; a total of 140 individuals, parents (N = 40) and teachers (N = 40), were chosen for the experimental group, while the remaining 40 parents and 20 teachers were assigned to the control group (CG), with an age range of 30 to 50 years old. Purposive sampling was used to determine the sample size. The data came from two schools in Islamabad and one in Rawalpindi, Pakistan. To treat their psychological concerns, parents and teachers were taught various therapeutic strategies. The participants filled the measure instruments of general health questionnaire (GHQ-28) after fifteen treatment sessions. SPSS version 25 was used to analyze the data, and the MANCOVA test was used to validate the results. Results: The results showed the interaction effect of participants (teachers and parents) and general health (, i.e., bodily symptoms, sleep and anxiety symptoms, inability to socialize, depression symptoms) was found to be non-significant with F (1, 154) = 2.13, p> .05, F (1, 154) = 3.12, p> .05, F (1, 154) = 0.17, p>.05, and F (1, 154) = 3.45, p> .05 respectively. Furthermore, there were no improvements in the control group. Practical Implication: The current study findings contribute in our understanding of the relationship between Psychotherapies and general health symptoms. The finding further implied for psychologist, and therapist that how much psychotherapies play role in reduction of severity level general health (, i.e., bodily symptoms, sleep and anxiety symptoms, inability to socialize, depression symptoms. Conclusion: The current study concluded that psycho-therapeutic techniques play a critical role in reducing the degree of general health symptoms among ASD teenagers’ parents and teachers. Keywords: Psychotherapeutic Interventions, General Health Symptoms, Parents, Teacher, ASD